2022
DOI: 10.1002/mde.3667
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐regional comparative study on digital finance and finance efficiency in China: The eastern and non‐eastern areas

Abstract: Digital finance is expected to improve the financial development of economic backward regions through its inclusive nature. Therefore, this paper selects the financial data of 30 provinces in China from 2011 to 2017 to evaluate regional finance disparities with the inclusion of digital finance, using the meta‐frontier slack‐based measure dynamic DEA model. The results are as follows. (1) The overall financial efficiency, input efficiency, output efficiency, and TGR in the eastern region are better than those i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…(1) The imbalance of development of digital financial inclusion in China. It was found that there are regional differences in the development of digital financial and the development of the eastern region is generally better than that of other regions, which is consistent with the study of Wang et al [5]. The digital financial inclusion in the western region has the fastest growth, but the development gap between western and eastern regions is still large.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…(1) The imbalance of development of digital financial inclusion in China. It was found that there are regional differences in the development of digital financial and the development of the eastern region is generally better than that of other regions, which is consistent with the study of Wang et al [5]. The digital financial inclusion in the western region has the fastest growth, but the development gap between western and eastern regions is still large.…”
Section: Discussionsupporting
confidence: 86%
“…Arguably, there are also national gaps in the development of digital inclusive finance. With regard to China's regions, the introduction of digital inclusion has resulted in better financial efficiency in the east regions than in the non-east regions, with the development of digital inclusive finance in the central and west regions lagging behind [5,35].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation